Evaluasi Usabilitas dan Perbaikan Tampilan Desain Antarmuka Pengguna Situs Web Eventmalang.net dengan Pendekatan Human-Centered Design, WEBUSE, dan Importance-Performance Analysis - Joshua Dika; Komang Candra Brata; Hanifah Muslimah Az-Zahra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
Visiting an event is an activity to increase your knowledge or just for refreshing. The high interest to visit an event that was held in Malang so Eventmalang.net was made. Eventmalang.net is a website to find what events to visit according to the people's interest in Malang. This research focuses on how to redesign Eventmalang.net's user interface with user involvement. This research used usability evaluation by using Web Usability Evaluation Tool and Importance-Performance Analysis for develop a system. The result of usability evaluation can be used to redesign user interface of Eventmalang.net. Method in this research is Human-Centered Design, which in its development process use user perspective to develop a system. Discussion in this research is about context of use, user requirements, original design evaluation, develop solution design, and solution design evaluation. The results show user interface that used Human-Centered Design method has better usability value than the original design. The success rate in effectiveness aspect has increase 40%. The average time result in efficiency aspect has increase 265.1% on first task and 843.2% on second task. In customer satisfaction, the usability level by WEBUSE has good and excellent performance and keep up the good work in IPA's quadran.